2010
DOI: 10.3109/10641955.2010.507835
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Management and Outcome of Pregnancies Complicated by Previous Abruption

Abstract: To prevent abruption recurrence, careful monitoring during hospitalization is important. Both clinical findings and transabdominal echography are useful in diagnosing abruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…There are few studies into the recurrence of abruption. 14,[25][26][27][28][29][30][31][32] To our knowledge, no prior large population-based studies have examined abruption recurrence risk in the United States. Almost all previous sizeable studies that have examined the recurrence of abruption were performed in European populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are few studies into the recurrence of abruption. 14,[25][26][27][28][29][30][31][32] To our knowledge, no prior large population-based studies have examined abruption recurrence risk in the United States. Almost all previous sizeable studies that have examined the recurrence of abruption were performed in European populations.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies from Finland and Japan examining the recurrence of placental abruption had very small numbers. [27][28][29] A study from South Africa found a recurrence rate of 35%. 30 However, that study may also be limited by small numbers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations